Developing Internet Banking within the Context of Building A Bank’s Competitive Advantage - KHAMITKHAN, Nazgul; BAKHYT, Eric; KARSHALOVA, Alma (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
This paper examines existing theoretical approaches to determining the essence of the concept of Internet banking as a banking service. The authors have conducted an analysis of the concept of Internet banking through the lens of its major characteristics in accordance with various approaches. The paper summarizes the scholarly/theoretical foundations of the effect of Internet banking on banks’ competitiveness; identifies some of the key trends in the development and areas for the implementation of the system of serving Internet banking clients; determines the methodological characteristics of reflecting the effect of Internet banking on banks’ competitiveness in putting together bank rankings; identifies some of the latest global trends in the market for Internet banking which are opening up new vistas of opportunity for its further development.